2008
DOI: 10.1016/j.jamcollsurg.2007.06.296
|View full text |Cite
|
Sign up to set email alerts
|

Partial Matrix Excision or Orthonyxia for Ingrowing Toenails

Abstract: BACKGROUND:We wanted to evaluate whether partial matrix excision and orthonyxia are equally effective in the treatment of ingrown toenails of the hallux. STUDY DESIGN: We conducted a prospective randomized clinical trial with 12-month observer-blinded followup, in the surgical outpatient department of a teaching hospital. We randomized 105 consecutive patients with a total of 109 ingrown toenails to either partial matrix excision (n ϭ 58) or an orthonyxia procedure (n ϭ 51). The main outcomes measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
0
32
0
3
Order By: Relevance
“…Kruijff et al . suggested that the best treatment for nail deformity should be both effective and painless.…”
Section: Discussionmentioning
confidence: 99%
“…Kruijff et al . suggested that the best treatment for nail deformity should be both effective and painless.…”
Section: Discussionmentioning
confidence: 99%
“…Evre 1 t›rnak batmas›nda; hafif eritem, ödem ve batan t›rnak çevresinde a¤r›, evre 2 t›rnak batmas›nda: eritem ve ödemin kötüleflme-sine ek olarak enfeksiyon ve drenaj, evre 3 t›rnak batmas›nda ise evre 2'deki bulgulara ek olarak lateral t›rnak kenar› hipertrofisi ve granulasyon dokusu mevcuttur 1,2,3,4 . Evre 2-3 t›rnak batmas› flikayeti mevcut olan hastalarda genellikle uygulanan matrisektomili veya matrisektomisiz parsiyel ya da total t›r-nak çekimi tel uygulamas›na göre, daha pahal›, kanama, enfeksiyon, a¤r› ve deformite gibi komplikasyonlar› olabilen ve cerrahi sonras› ifl kayb›na yol açan yöntemlerdir 5,6,7 . Erken evre enfeksiyon geliflimi olmayan olgularda tel uygulamas› operasyona göre yaklafl›k üçte bir oran›nda ucuz görünmekte iken, komplike ve enfekte olgularda bu maliyet fark› 4-5 kata kadar ç›kabilmektedir.…”
Section: Giriflunclassified
“…Bizim bu çal›flmam›zda etkinli¤ini de¤erlendirmeyi amaçlad›¤›m›z t›rnak teli uygulamas› t›rnak batmas› tedavisinde kolay ve ucuz bir tedavi alternatifidir. Dünya literatürlerinde de t›rnak tellerinin t›rnak batmas›nda baflar›yla uyguland›¤›na dair yay›nlar bulunmaktad›r 2,5,6,8 . Çal›flmam›zda , 1) De¤iflik kal›nl›ktaki batan t›rnaklarda t›rnak teli uygulamas›n›n etkinli¤i, 2) Tedavi kesilmesinden sonra nüks s›kl›¤›n›n saptanmas›, 3) Nüks için mevcut risk faktörlerinin tan›mlanmas› amaçlan-maktad›r.…”
Section: Giriflunclassified
See 1 more Smart Citation
“…Hyperplasia occurs as a result of irritation of the nail groove and the reaction of the surrounding soft tissues. Finally, the nail substance enters the nail groove and causes infection (5)(6)(7)(8)(9)(10). Although there are many conservative and surgical treatments for ingrown toenails, the optimum treatment method has not been clearly defined because of the high recurrence rates, low degrees of patient satisfaction, and reported cosmetic issues.…”
Section: Introductionmentioning
confidence: 99%